Effects of exposure to sediment-associated fipronil on cardiac function of Neotropical armored catfish Hypostomus regani - Ferro, Lucas Abreu [UNESP]; Fernandes, Suzana Luisa Alves [UNESP]; Kalinin, Ana Lúcia; Monteiro, Diana Amaral (Taylor & Francis, 2023)
Fipronil is widely used as a broad-spectrum insecticide in agriculture, urban environments, and veterinary medicine. Fipronil can enter aquatic ecosystems and spread to sediment and organic matter, representing a risk to non-target species. This study aimed to evaluate the effects of short-term (96 h) exposure to a low and realistic concentration of sediment-associated fipronil (4.2 µg.kg−1 of Regent® 800 WG) on myocardial contractility of armored catfish Hypostomus regain, a benthic fish species. Fipronil exposure induced increased inotropism and acceleration of contractile kinetics, although no alterations in the relative ventricular mass were observed. This better cardiac function was associated with an elevated expression and/or function of the Na+/Ca2+ exchanger and its marked contribution to contraction and relaxation, probably due to a stress-induced adrenergic stimulation. Ventricle strips of exposed fish also exhibited a faster relaxation and a higher cardiac pumping capacity, indicating that armored catfish were able to perform cardiac adjustments to face the exposure. However, a high energetic cost to maintain an increased cardiac performance can make fish more susceptible to other stressors, impairing developmental processes and/or survival. These findings highlight the need for regulations of emerging contaminants, such as fipronil, to ensure adequate protection of the aquatic system.
Keywords: calcium handling; cardiac pumping capacity; contaminated sediments; contractile force; excitation-contraction coupling; fish; heart; Insecticide; Na+/Ca2+ exchanger; physiological biomarkers